Kajian Implementasi Sistem Manajemen Keselamatan (ISM Code) dalam Upaya Mencegah Kecelakaan Pelayaran di Indonesia: Tinjauan Literatur - Fitriah, Rifkah; Fadjri, Tarisha Ananda (Politeknik Pelayaran Sumatera Barat, 2025)
This study aims to examine the implementation of the International Safety Management (ISM) Code as a strategy for reducing maritime accidents in Indonesia, using a Systematic Literature Review (SLR) guided by the PRISMA framework. The review covers publications from 2020–2025, including international and national journal articles, government reports, and official IMO documents. The findings indicate that, although the ISM Code has been formally adopted in Indonesia, its implementation continues to face significant challenges, such as limited crew training, weak supervision, inadequate procedural understanding, and insufficient commitment to a safety culture. Thematic analysis highlights four key areas of focus: compliance with safety standards and regulations, operational safety of ships, the development of safety culture within shipping companies, and the use of digital technologies in safety management. The study concludes that the ISM Code makes a positive contribution to preventing maritime accidents; however, its effectiveness relies on managerial support, improved human resource competence, and consistent auditing. Strategic recommendations include enhancing training programs, ensuring regular vessel maintenance, conducting continuous audits, and fostering a strong safety culture. The results of this study are expected to provide valuable insights for policymakers, shipping companies, and scholars in strengthening maritime safety in Indonesia.